The Management of Psychosocial Case with the Mental Health and Psychosocial Support During Covid-19 Pandemic - Dwi Heppy Rochmawati; Heri Setiawan; Tri Andri Pujiyanti; Sulastri Sulastri (Indonesian Journal of Global Health Research, 2021)
Since the declaration of the pandemic condition by WHO on March 11, 2020, it has caused various responses from people throughout the world. The spread of the virus is very fast, wide and mass causing more cases and affecting not only physical condition but also psychosocial condition. Various psychosocial problems are experienced by the community related to pandemic conditions. The purpose of this paper was to describe the management of mental health care and psychosocial support for the handling of psychosocial problems experienced by the community during Covid-19 pandemic. The study used quantitative methods of pretest post-test experiment without control group, by providing mental health and psychosocial support. The research sample of 95 respondents was taken by total sampling. The package of activities provided: Mental and Psychosocial Health Support (DKJPS) for Healthy People, DKJPS for Travel Players, DKJPS in Close Contact, DKJPS in Probable Cases, DKJPS in Covid-19 Confirmed Cases and DKJPS for Vulnerable Groups. Therapy was given to 95 respondents (22 volunteers, 51 volunteer nuclear families and 22 volunteer assisted families) using the 29-question of Self-Reporting Questionnaire (SRQ) measurement tool. The results showed that the provision of mental health and psychosocial support had an impact on reducing respondents' psychosocial problems, in the pretest measurement as much as 6.3% of respondents experienced psychosocial problems to 0% of respondents on the post-test. The analysis was carried out using the Wilcoxon test and obtained a p-value of 0.014 (<0.05), which means that there is an effect of mental health and psychosocial support on the handling of psychosocial problems.